Making Something out of Nothing: Neutral Content Modulates Attention in Generalized Anxiety Disorder - Olatunji, Bunmi O. (Depress Anxiety, 2011)
Although an attentional bias for threat has been implicated in generalized anxiety disorder (GAD), evidence supporting such a bias has been inconsistent. The current study examines whether exposure to different emotional content modulates attention disengagement and impairs the perception of subsequently presented nonemotional targets in GAD. Patients with GAD (n = 30) and controls (n = 30) searched for a target embedded within a series of rapidly presented images. Critically, an erotic, fear, disgust, or neutral distracter image appeared 200 ms or 800 ms before the target. Impaired target detection was observed among GAD patients relative to controls following only fear and neutral distractors. However, this effect did not significantly vary as a function of distractor stimulus duration before the target. Furthermore, group differences in target detection after fear distractors were no longer significant when controlling for target detection after neutral distractors. Subsequent analysis also revealed that the impaired target detection among those with GAD relative to controls following neutral (but not fear) distractors was mediated by deficits in attentional control. The implications of these findings for further delineating the function of attentional biases in GAD are discussed.